2020
DOI: 10.1177/2059700220939404
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of hydration in concussions and long-term symptoms of concussion for athletes. A review of the evidence

Abstract: The purpose of this review is to address what is known, speculated, and hypothesized regarding the issue of hydration and concussions. Based on the question, “What impact does hydration have on the relative risk for suffering concussive injuries along with long-term ramifications that have been associated with concussive (and repeated subconcussive) traumas to the cerebral cortex?,” a search of available literature was performed through June 2019. Deducing from the available literature, we can stipulate that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
(396 reference statements)
0
2
0
Order By: Relevance
“…Although the term concussion has been documented in sports for many years, it has become increasingly synonymous with sports recently. Noteworthy, only 15.5% are sports-related concussions (SRCs) [15]. Sport-related concussion refers to a TBI caused by biochemical forces to the head or surrounding areas experienced during a sporting activity [16].…”
Section: Traumatic Brain Injury-definition and Diagnosingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the term concussion has been documented in sports for many years, it has become increasingly synonymous with sports recently. Noteworthy, only 15.5% are sports-related concussions (SRCs) [15]. Sport-related concussion refers to a TBI caused by biochemical forces to the head or surrounding areas experienced during a sporting activity [16].…”
Section: Traumatic Brain Injury-definition and Diagnosingmentioning
confidence: 99%
“…The risk of SRC is highest in collision sports. Among the most common of these are American football, rugby, soccer and Australian Rules football [15]. Recent research found that the rate of concussion was 0.06 concussions per 1000 h. Additionally, players were 78 times more likely to sustain one during a match versus training [18].…”
Section: Traumatic Brain Injury-definition and Diagnosingmentioning
confidence: 99%